Lack of Association Between Sex Hormones, MDSCs, LDGs and pDCs in Males and Females With Systemic Lupus Erythematosus - Jones, Jessica M.; Smith, Frances; Littlejohn, Emily; Jorgensen, Trine N. (Frontiers in Immunology, 2022)
Plasmacytoid dendritic cells (pDCs) and low-density granulocytes (LDGs) are interferon-alpha producing cells that create a pro-inflammatory response in Systemic Lupus Erythematosus (SLE) leading to auto-antibody production and organ damage. Both pDCs and LDGs have been shown to be dysfunctional in patients with active SLE. Myeloid-derived suppressor cells (MDSCs) have the capacity to control T and B cell activation and differentiation, and have recently been identified as cells of interest in SLE as well. While not fully understood, previous studies have suggested that pDCs are regulated in part by both X chromosome inactivation and estradiol. Whether sex chromosomes or sex hormones regulate MDSCs and LDGs remain to be determined. We aimed to explore the relative role of sex and sex hormones on pDC, MDSC and LDG frequency and function in SLE patients. We recruited patients with SLE as defined by ACR or SLICC classification criteria and healthy controls in conjunction with the Cleveland Clinic Lupus Cohort and Clinical Research Unit. We analyzed serum sex hormone levels by ELISA, and frequencies of pDCs, MDSCs, and LDGs among PBMCs and serum cytokine levels by flow cytometry. PBMCs were further analyzed for expression of genes involved in or induced by toll-like receptor (TLR)7 or TLR9 stimulation. In all SLE patients, the serum estradiol/testosterone ratio and levels of granulocytic MDSCs and LDGs were increased, while levels of pDCs were decreased. Furthermore, pDCs from active SLE patients expressed lower levels of TLR7 and TLR9 and showed diminished production of TLR9-induced IFNα and TNFα as compared to healthy controls. LDGs from healthy controls and SLE patients expressed very low levels of TLR7 and TLR9 and largely failed to respond to TLR9 stimulation. Thus, regardless of sex and sex-hormone levels, frequencies of pDCs, MDSCs and LDGs, TLR7 and TLR9 expression, and TLR9-driven cytokine production were similarly altered in male and female SLE patients.